Urgency of Regulating Cryptocurrency Inheritance Features on Exchange Platforms to Ensure Legal Certainty for Heirs in Indonesia - Syaiful Malik; Taupiqqurrahman (Journal of Law, Politic and Humanities, 2026)
The development of cryptocurrency as a digital asset presents new challenges in inheritance law. Its decentralized nature and reliance on private keys pose a risk of rendering the asset permanently inaccessible if the owner passes away. This article, titled "Urgency of Regulating Cryptocurrency Inheritance Features on Exchange Platforms to Ensure Legal Certainty for Heirs in Indonesia," aims to analyze the juridical implications of the absence of automated inheritance claim features on exchange platforms and the urgency of their regulation. This normative legal research employs statutory, conceptual, and comparative approaches to compare the governance mechanisms of inheritance claims on global and local crypto exchanges. The results indicate that the absence of specific regulations creates a legal vacuum that heightens uncertainty regarding heirs' civil rights. Comparative analysis reveals that local platforms still rely on manual administrative procedures, which can lead to legal constraints, whereas global platforms have integrated legal compliance systems. In conclusion, regulations mandating the availability of inheritance features on exchange platforms are essential for providing legal protection, preventing material loss, and ensuring legal certainty for heirs.